2016
DOI: 10.1051/matecconf/20167304018
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of strength and crack resistance of normal sections of bent elements of T-sections, made of rubber concrete, kauton reinforcement and concrete

Abstract: Abstract.One of the urgent tasks of development of the construction associated with the development of new building designs, the use of which provides increased strength, crack resistance, reducing the flow of construction materials, reducing the labor intensity, energy consumption and cost. Ensuring effective functioning of structures during their operation in the harsh environments associated not only with the task of developing materials of higher strength and corrosion resistance, but also composites of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…As a result of studies of rubber concrete [1,2] and structures based on it [3,4,5,6,7,8], including reinforced rubcon bending elements of rectangular cross section [3,4] and T-sections [5], the authors confirmed the possibility of using structures based on this polymer concrete, the type of sensors was established to obtain an adequate picture of the distribution of deformations in the sections of the element. Also, methods have been proposed for using polymer concrete only in the tensile zone to protect steel reinforcement [6] or a polymer casing to protect concrete from aggressive environmental influences and increase the strength of the tensile zone [7,8,9].…”
Section: Introductionmentioning
confidence: 81%
“…As a result of studies of rubber concrete [1,2] and structures based on it [3,4,5,6,7,8], including reinforced rubcon bending elements of rectangular cross section [3,4] and T-sections [5], the authors confirmed the possibility of using structures based on this polymer concrete, the type of sensors was established to obtain an adequate picture of the distribution of deformations in the sections of the element. Also, methods have been proposed for using polymer concrete only in the tensile zone to protect steel reinforcement [6] or a polymer casing to protect concrete from aggressive environmental influences and increase the strength of the tensile zone [7,8,9].…”
Section: Introductionmentioning
confidence: 81%
“…The geometric parameters of the beams were assigned based on the analysis of literature sources [4,5,6,8,9,10,11] 60x120mm, where the larger size is the height of the section, the total length of the element is 1.4 m. Based on the analysis of work [11], the deflectometer is set only in the middle of the span.…”
Section: Methodsmentioning
confidence: 99%
“…The beams were tested for pure bending -the most characteristic type of loading for such elements [9,10,11,12,13,14,15,16], this test scheme also corresponds to the papers devoted to the study of the "work" of rubcon beams under load [4,5,6].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…without fiber reinforcement, with fiber reinforcement of only the tensile zone and with fiber reinforcement along the entire height of the section. The geometrical parameters of the beams were assigned based on the analysis of literature sources [9][10][11][12][13]. It should be noted that the fiber is located chaotically.…”
Section: Experimental Partmentioning
confidence: 99%